Organization of Gynaecological Cancer Care 2020
DOI: 10.1136/ijgc-2020-esgo.232
|View full text |Cite
|
Sign up to set email alerts
|

604 Significant variation in treatment and survival outcomes in stage 2–4 ovarian cancer in england: results from the national ovarian cancer feasibility audit pilot

Abstract: OR "Angiomyofibroblastoma of the vulva with sarcomatous transformation". Results A total of 69 reported cases were found. In our knowledge, the case presented is the first report of AMFB in Colombia. The age of the patients ranged between 16 and 82 years, with an average of 43 years. The main presenting symptom was the presence of a non-painful vulvar mass, although some of the patients in the reported cases reported pain and dyspareunia (8/69). The evolution time varied between 1 month and 9 years with an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These studies assessed survival after primary cytoreductive surgery followed by adjuvant platinum-based chemotherapy in women with advanced EOC. The Sundar et al 13 underpinning the NMA and the results of our updated analysis provides more precise and reliable estimates than seen in previous studies and reviews in this area, 6,8–12,97 which should enable more informed decisions to be made. Although the findings do not enable us to determine whether the survival benefit is a direct effect of the surgical intervention, they may encourage the surgical community to strive toward improving rates of complete cytoreduction and perhaps more centers adopting a more aggressive approach to attempt to improve rates of complete cytoreduction.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…These studies assessed survival after primary cytoreductive surgery followed by adjuvant platinum-based chemotherapy in women with advanced EOC. The Sundar et al 13 underpinning the NMA and the results of our updated analysis provides more precise and reliable estimates than seen in previous studies and reviews in this area, 6,8–12,97 which should enable more informed decisions to be made. Although the findings do not enable us to determine whether the survival benefit is a direct effect of the surgical intervention, they may encourage the surgical community to strive toward improving rates of complete cytoreduction and perhaps more centers adopting a more aggressive approach to attempt to improve rates of complete cytoreduction.…”
Section: Discussionmentioning
confidence: 69%
“…Despite the obvious challenges, this should be considered more than feasible because on average only around half of women with stage II–IV and unstaged ovarian cancer receive surgery in England. 13 Existing trials have shown conflicting results when further surgery was performed as an interval procedure after suboptimal cytoreduction at primary surgery. 111 Therefore, it seems best to increase attempts at optimizing to lower levels of RD at first surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations